1984
DOI: 10.1103/physrevlett.53.588
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Shear in a Two-Dimensional Electron Solid

Abstract: Shear waves are shown to propagate in the two-dimensional electron solid on liquid helium. Their velocity and damping are measured and used to deduce the shear components of the viscoelastic tensor up to melting. A linear temperature variation at low temperatures contrasts with the premelting region, where the sharper renormalization of the elastic component is accompanied by a very rapid increase in the viscous component.PACS 63.20.Dj, 64.70.Dv A material is solid if it returns to its original shape upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…The regime of N, p, T parameters suitable for the creation of a ripplopolaron Wigner lattice lies within the regime that would be achievable in recently proposed experiments, aimed at stabilizing multielectron bubbles [76]. The ripplopolaron Wigner lattice and its melting transition might be detected by spectroscopic techniques [82,86] probing for example the transverse phonon modes of the lattice [87].…”
Section: Ripplopolarons In Multi-electron Bubbles In Liquid Heliummentioning
confidence: 99%
“…The regime of N, p, T parameters suitable for the creation of a ripplopolaron Wigner lattice lies within the regime that would be achievable in recently proposed experiments, aimed at stabilizing multielectron bubbles [76]. The ripplopolaron Wigner lattice and its melting transition might be detected by spectroscopic techniques [82,86] probing for example the transverse phonon modes of the lattice [87].…”
Section: Ripplopolarons In Multi-electron Bubbles In Liquid Heliummentioning
confidence: 99%
“…Well-known examples of charged periodic structures are the Wigner crystal, [9][10][11]33,34 charged colloidal crystals, 35 and charge density waves. [36][37][38] In many charged systems, unscreened Coulomb interactions are present:…”
Section: Elasticity and Disorder In Periodic Systemsmentioning
confidence: 99%
“…Examples of physical systems range from domain walls in magnetic and ferroelectric materials, 1,2 contact lines of a liquid meniscus on a rough substrate, 3 crack propagation, 4 to vortex lattices in type-II superconductors, 5,6 charge density waves ͑CDWs͒, 7,8 and Wigner crystals. [9][10][11][12] In these systems, the competition between elastic interactions which tend to impose some long-range order in the system and quenched disorder, leads to the formation of glassy phases. Two broad classes of elastic systems can be distinguished: random manifold systems such as domain walls, contact lines, and cracks, and periodic systems such as vortex lattices, charge density waves, and Wigner crystals.…”
Section: Introductionmentioning
confidence: 99%
“…For each profile two measurements are shown. One at a temperature of 563 mK, far above the melting temperature for a density of 1.3ϫ10 12 m Ϫ2 (T c ϭ260 mK͒. The other measurement ͑at either 250 or 205 mK͒ is done below this melting temperature.…”
Section: Different Density Profilesmentioning
confidence: 99%
“…8 Another advantage is the possibility of varying the screening, going from an unscreened system ͑bulk helium͒ to a screened system ͑helium films͒. 9,10 So far, a number of methods have been used to observe and investigate the properties of the crystal: plasma resonances of the crystal ͑coupled to the capillary waves on the He surface͒, 7,11 measurements of the shear in the crystal, 12,13 mobility measurements, 14 and recently, measurements of the magnetoconductivity. [15][16][17] The measurements of the magnetoconductivity have shown that although the conductivity is different from the conductivity in the fluid, the crystal is still an excellent conductor.…”
Section: Introductionmentioning
confidence: 99%